Selective targeting of melanoma using N-(2-diethylaminoethyl) 4-[(18)F]fluoroethoxy benzamide (4-[(18)F]FEBZA): a novel PET imaging probe - Garg, Pradeep K. (EJNMMI Res, 2017)
BACKGROUND: The purpose of this study was to develop a positron emission tomography (PET) imaging probe that is easy to synthesize and selectively targets melanoma in vivo. Herein, we report the synthesis and preclinical evaluation of N-(2-diethylaminoethyl) 4-[(18)F]Fluoroethoxy benzamide (4-[(18)F]FEBZA). A one-step synthesis was developed to prepare 4-[(18)F]FEBZA in high radiochemical yields and specific activity. The binding affinity, the in vitro binding, and internalization studies were performed using B16F1 melanoma cell line. The biodistribution studies were performed in C57BL/6 normal mice, C57BL/6 mice bearing B16F1 melanoma tumor xenografts, and nu/nu athymic mice bearing HT-29 human adenocarcinoma tumor and C-32 amelanotic melanoma tumor xenografts. MicroPET studies were performed in mice bearing B16F1 and HT-29 tumor xenografts. RESULTS: 4-[(18)F]FEBZA was prepared in 53 ± 14% radiochemical yields and a specific activity of 8.7 ± 1.1 Ci/μmol. The overall synthesis time for 4-[(18)F]FEBZA was 54 ± 7 min. The in vitro binding to B16F1 cells was 60.03 ± 0.48% after 1 h incubation at 37 °C. The in vivo biodistribution studies show a rapid and high uptake of F-18 in B16F1 tumor with 8.66 ± 1.02%IA/g in this tumor at 1 h. In contrast, the uptake at 1 h in HT-29 colorectal adenocarcinoma and C-32 amelanotic melanoma tumors was significantly lower with 3.68 ± 0.47%IA/g and 3.91 ± 0.23%IA/g in HT-29 and C-32 tumors, respectively. On microPET images, the melanoma tumor was clearly visible by 10 min post-injection and the intensity in the tumor continued to increase with time. In contrast, the HT-29 tumor was not visible on the microPET scans. CONCLUSIONS: A rapid and facile synthesis of 4-[(18)F]FEBZA is developed. This method offers a reliable production of 4-[(18)F]FEBZA in high radiochemical yields and specific activity. A high binding affinity to melanoma cells and high uptake in tumor was noted. The microPET scan clearly delineates the melanoma tumor by 10 min post-injection. The results from these preclinical studies support the potential of 4-[(18)F]FEBZA as an effective probe to image melanoma.